A judicialização do direito à educação básica e seus reflexos no processo de desenvolvimento sustentável - Rios, Christian Robert dos (2016)
The current theoretical division of human rights in different dimensions moves away from the notion of generational succession, and approaches the ideas of expansion, cumulation and complementarity. The universality of fundamental rights is comprehended in the plane of unity and indivisibility, being a result of the formalization and institutionalization of the human rights in a determined historical, social, political, cultural and juridical context. In a permanent dinamic of interaction, the group of basic rights is not represented by isolated and restricted categories, but it makes a interrelated entire. It is in this process that basic rights are forming and shaping the fundamental rights. The first dimension rights, after the liberalism crisis, were complemented by the second dimension rights, including among these the right to education as a way of human development, leading to a bigger equality between the people .In the continuous process of human rights expansion, the third dimension rights arises. The third dimension rights include the right to development, this understood as a process founded on the ideals of solidarity and aimed at reducing inequalities and poverty. The sustainability adheres to the development concept to situate it as a harmonious process of meeting the aspirations of present and future generations. The sustainable development marks the congruence between the right to education and the right of development, relating the solidary advancement of culture, science and technology to the expansion of personal capacities and skills. Under the federal constitution's Empire, the social rights are subject to immediate enforcement regime (art. 5, § 1), setting enforceable rights of state entities. Being a subjective right constitutionally guaranteed, once judicialized, the right to basic education should receive from the authentic interpreter a significance, guided by the classic methods of interpretation and by the very instruments of constitutional hermeneutics, thus providing the normative force of the Constitution. The Federal Supreme Court, in the precedents it judged, adopted the understanding that education is an inexcusable political and legal obligation that binds all public officials, being exceptional responsability of the Judiciary enforce this provision, without being able to speak in violation of the principle of separation of Powers or call the reservation possible. By estabilishing the right to education, the state enforces the fundamental objectives of the Federative Republic of Brazil, especially the development as part listed explicitly in art. 3, II of the Federal Constitution.